Should peristomal infection after percutaneous endoscopic gastrostomy be considered a healthcare-associated infection? Role of antibiotic prophylaxis. Issue 2 (12th March 2012) - Duarte, H.; Alcobia, A.; Fonseca, J.; Capelas, M.L.
Abstract : Background: Percutaneous endoscopic gastrostomy is a widely used method for inserting a gastrostomy tube in patients who are unable to eat but have a normally functioning gut. Peristomal wound infection is the most common complication. Risk factors for local infection are largely unknown. Evidence suggests that antibiotic prophylaxis and preventive strategies related to infection control may reduce infection rates. Purpose: To evaluate the incidence of peristomal infection and to discover the potential patient risk factors following PEG tube placement. Materials and methods: An observational analytic prospective study was carried out at Garcia de Orta hospital between October 2010 and May 2011 and 31 patients were included. A minor adaptation of the Centres for Disease Control (CDC) definitions for superficial surgical site infection was used to detect PEG site infections. Medical records were reviewed for demographic data, use of prophylactic antibiotics, complications and comorbid conditions. Statistical analysis SPSS 17. Results: Peristomal infections were identified in 15/31 (48.38%). A global incidence rate (30 days) of 16.12 per 1000 days and an incidence density of 9.44 were found. Wound isolates included Pseudomonas aeruginosa (39.1%) and Staphylococcus aureus (61%) of which 50% were methicillin-resistant (MRSA). Of the patients who had received antibiotic prophylaxis (51.8%), 55.5% developed PEG-site infections. Diabetes mellitus and obesity were significantly associated with peristomal infections (p<0.05). Conclusions: Patients with diabetes mellitus and a BMI>30 kg/m 2 had a higher risk of peristomal wound infections after percutaneous endoscopic gastrostomy. High incidence of MRSA (30.4%) illustrates the need to review the antibiotic prophylaxis protocol but the efforts to reduce MRSA occurrence with infection control measures and an epidemiological surveillance program should remain a priority.